Efecto del extracto de Allium sativum “ajos” para el control de monogenoideos branquiales (Platyhelminthes) en Pterophylum scalare adquiridos de un centro de acopio, Iquitos-Perú - Espinoza Zavaleta, Maximiliano (2025)
Pterophyllum scalare, popularly known as angelfish or scalar, is a species of Cichliformes in high demand in the ornamental market in the Peruvian Amazon and worldwide. Its captive breeding is threatened by massive infestations of parasites, including monogenoids and ectoparasites that parasitize the fish's gills, compromising their respiration. Given the need for effective, low-cost, and environmentally friendly treatments. The present study aimed to evaluate the effect of Allium sativum “garlic” for the control of gill monogenoids in P. scalare. The fish were collected in April 2024 at the Catfish Aquarium, located at “Las Flores “street N°22 in the district of San Juan Bautista, Iquitos - Peru. The acquired fish were transferred to the laboratory of Parasitology and Aquaculture Health of the Research Center “Fernando Alcántara Bocanegra” (CIFAB) of the “Instituto de Investigaciones de la Amazonía Peruana” (IIAP), where they were kept for 15 days in 100 L fish tanks under stress conditions, thus increasing the parasitic load present in the fish, after this period the fish were subjected to treatments based on garlic extract, using 100 g of garlic in 1 L. of water as a stock solution, from which three treatments were determined: T1 = 10 ml/L, T2 = 20 ml/L and T3 = 30 ml/L. For the in vitro tests, the time of action of the garlic extract to kill the gill monogenoids was determined, which resulted in an average time of 30 minutes for T1, 22.3 minutes for T2, and 9.6 minutes for T3. For the in vivo tests, the fish were subjected to the treatments daily with 30-minute baths for 5 days, using the same stipulated doses: T1 = 10 ml/L, T2 = 20 ml/L, and T3 = 30 ml/L. At the end of the experiment, the fish were sacrificed for the removal and consequent conservation of the gills for the respective parasitological analysis. The results of the study allowed the identification of the monogenoids Gussevia spiralocirra and Sciadicleithrum iphthium. The evaluation of the treatments determined that treatment 3 (30 ml/L) showed the best results reducing considerably the parasite load with an efficacy of 98%. It is concluded that the A. sativum extract is effective in the three doses used; however, the use of 30 ml/L is recommended since it eliminates the greatest number of parasites and at the same time does not cause mortality or apparent damage to the fish exposed to this product.